Feasibility Study on Magnetorheological Finishing of Thin Copper Substrate - Bo Pan; Renke Kang; Yunfei Zhang; Kailong Li; Dongxing Du; Xiaoguang Guo; Chao Wang; Jiang Guo; Xianglong Zhu; Wen Huang (Chinese Journal of Mechanical Engineering)
Abstract Thin copper substrates with high accuracy are highly required in precision physical experiments. However, even using double-sided lapping, the flatness is still limited due to the accuracy of lapping plate, process vibration and so on. Hence, as a subsequent process, this paper employs magnetorheological finishing (MRF) to further improve the flatness. Nevertheless, thin copper substrates, which are sensitive to the stress, deformed easily with uneven material removal on the surface. Therefore, MRF is adopted on machining thin copper substrate for the first time considering deformation induced by stress. A finite element model is established to evaluate the deformation by residual stress, and the results show that the deformation tends to be more serious with the increase of the material removal. According to the simulation results, the material removal is optimized considering both deformation and efficiency, and a series of experiments are conducted on a Φ100×2.8 mm workpiece to verify the simulation results. The experimental results show that the flatness is further improved from peak to valley (PV) 6.6 μm to PV 2.3 μm with optimized processing parameters. Hence, the feasibility of magnetorheological finishing on thin copper substrate is demonstrated.